Pengembangan Strategi Agribisnis Sapi Potong di Kabupaten Bondowoso - Asmaul Khusna; Heny Kuswanti Daryanto; Merry Muspita Dyah Utami (Institut Pertanian Bogor, 2016)
Bondowoso district has a primary program to become the center of beef cattle to increase the national of beef supply. The fulfillment of beef supply can be achieved by agribusiness development strategy in Bondowoso district. This study has three main objectives that include the following: a) Identify the external and internal factors that affect the development agribusiness of beef cattle in Bondowoso district; b) Analyze the alternative strategies for improving agribusiness of beef cattle in Bondowoso district; and c) Determine strategies priorities that can be applied in development agribusiness of beef cattle in Bondowoso district. The analysis that performed in analysis of data is: IFE, EFE, IE, SWOT, and QSPM. Based on SWOT matrix analysis there are five alternative strategies: the integration between agribusiness sub system, the strategy to increase the number of the population, training in managerial and technology, increasing the quantity, and the quality of production. The strategy priority were used Quantitative Strategies Planning Matrix (QSPM) analysis was the integration on agribusiness sub system. The sub system integration can be done by integrating the department of livestock and fisheries with the department of forestry and plantation area to make a husbandry which integrated with plants. Department of livestock and fisheries also can cooperate with the promotion and investment to invite the investor to establish business or industry in Bondowoso. The Government can cooperate with university to conduct information and provide training the farmers. If all aspects in subsystem could be synergistic the Development of Beef Cattle Agribusiness in Bondowoso district can be implemented well.